2022
DOI: 10.3390/jcm11247278
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Practices among Multiple Sclerosis Patients and Professionals

Abstract: Vitamin D serum level increase is associated with a reduction in clinical relapse rate, gadolinium-enhancing lesions, new or enlarging T2 lesions and new active lesions in the MRI in MS patients. However, current RCTs assessing the vitamin D supplementation therapeutic effect in MS provide inconclusive results. Experts recommend vitamin D measurements and implementations among patients with MS. This article discusses an observational study, performed without any intervention to evaluate the vitamin D status an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Furthermore, 95 out of 133 patients declared vitamin D supplementation (71.4%) in the study group. This percentage is comparable with another study in the Polish population, in which 103 out of 139 patients were supplementing vitamin D [ 41 ]. A lower percentage of MS patients supplementing vitamin D was reported by Pape et al (60.0%) [ 42 ] and Masullo et al (52.78%) [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, 95 out of 133 patients declared vitamin D supplementation (71.4%) in the study group. This percentage is comparable with another study in the Polish population, in which 103 out of 139 patients were supplementing vitamin D [ 41 ]. A lower percentage of MS patients supplementing vitamin D was reported by Pape et al (60.0%) [ 42 ] and Masullo et al (52.78%) [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…GM appeared to be a pivotal element influenced not only by the type of diet but also by therapies. In fact, vitamin D supplementation, commonly prescribed for MS [ 121 ], may also influence gut bacterial populations by increasing the frequency of certain genera [ 122 ]. In vitro studies have shown that some MS drugs (e.g., fingolimod and teriflunomide) also have anti-inflammatory and antioxidant effects and can shape GM and inhibit the growth of neurotoxin-secreting gut bacteria.…”
Section: Diets and Dietary Supplementationsmentioning
confidence: 99%